(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the characteristics of core muscle dysfunction in patients with chronic low back pain. Objects and methods: A descriptive cross-sectional study on 71 patients with chronic low back pain at the Rehabilitation clinic of the University Medical Center Ho Chi Minh city, from February 2023 to the end of August 2023. Results: Patients exhibit core muscle dysfunction when they have at least one of the following conditions: decreased core muscle endurance, weak local core muscles, and poor core stability. Regarding core muscle endurance, the percentage of patients whose endurance time for the Extensor test and the Flexor test fell below the reference values for the normal Brazilian population was 100%, with average times of 50 ± 23s and 35 ± 18s, respectively. The percentage of patients whose endurance time for the Right and Left side-bridge test fell below the reference values for the normal Brazilian population was 90.1%, with average times of 30 ± 16s and 29 ± 17s, respectively. Regarding local core muscle, 40.8% of patients had weak local core muscles when performing the abdominal drawing-in maneuver with a pressure biofeedback unit. Most patients with weak local core muscles tended to use compensatory muscle activation patterns when performing the abdominal drawing-in maneuver, including breath holding (82.8%), thoracic-lumbar spine flexion (51.7%), posterior pelvic tilt (27.6%), and abdominal bulging (24.1%). Regarding core stability, 32.4% of patients had poor core stability according to the Sahrmann core stability test. Conclusions: A high percentage of patients with chronic low back pain have core muscle dysfunction. The recorded endurance times were 50 ± 23s for the extensor test, 35 ± 18s for the flexor test, 30 ± 16s for the right side-bridge test, and 29 ± 17s for the left side-bridge test. The percentage of patients with weak local core muscles when performing the abdominal drawing-in maneuver with a pressure biofeedback unit was 40.8%. The percentage of patients with poor core stability according to the Sahrmann core stability test was 32.4%.